A conceptual analysis of strategic capability development within product innovation projects. (1st June 2014) - Kashan, Alireza Javanmardi; Mohannak, Kavoos
Abstract : Strategic capability development refers to the renewal of the organisational capabilities which are sources of competitive advantage. The aim of this paper is to examine how strategic capability and competitive advantage build up over time. Recent literature points to the integration of dynamic capability and ambidexterity perspectives in explaining organisational capability development. Literature analysis reveals the role of knowledge integration and product innovation in integrating dynamic capability and ambidexterity. However, little attention has yet been paid to knowledge integration within innovation projects as a context for capability development. Accordingly, this paper aims to develop a conceptual framework for strategic capability development focusing on the role of knowledge integration within product innovation projects. This framework contributes to identifying and emphasising the role of micro processes in capability renewal which in turn enhances our understanding of strategic capability development.